MATERIALISM AS SEEN IN THE BLACK TULIP BY ALEXANDER DUMAS - Meta Kurnia Sari (Lexicon, 2012)
This study aims to observe the Materialism among the main characters in Alexandre Dumas’ novel, The Black Tulip. In the research process, the writer finds the data by reading books which related to the topic as well as the through the internet.This study basically adopts “Dynamic Structuralism” which includes three elements; the reader, the work, and the reality. The method of research is conducted through library research, with The Black Tulip as the primary data, and the references that support the analysis as the secondary data.The result of this study shows that the materialism exists in everyone. People need money in order to support their life. Money is indeed important and it is employed as the parameter of success in some aspects of life. However, the level of materialism in every single person is different. This paper shows how significant a black tulip is for certain main characters, including the ways they treat it. It is also the symbol of sadness in the Netherlands in 1672-1673 which was identical with the dark age. Besides, it is also as the symbol of Rosa, the prison keeper daughter who helps Van Baerle in revealing the truth over the black tulip.